International perspectives of the European Monetary System - Hartmut Picht (Intereconomics, 1982)
The none too firmly established position of the IMF with regard to the realization of the objectives of its Articles of Agreement has been additionally impaired by the establishment of the European Monetary System. From an international point of view a revision of the present EMS concept would seem to be called for in order to prevent the credibility of the IMF and the objectives of its Agreement being called in question.
Keywords: 330; Monetary Policy